The effect of sources and rates of phosphorus application on the production of rice in Rio Grande do Sul - Goedert, Wenceslau J.; Patella, José Francisco; Moraes, José Francisco V. (Pesquisa Agropecuaria Brasileira, 2014)
This eight year study was started in 1960 to determine the influence of sources and rates of phosphorus application on the production of rice. The experiment was conducted on a planosol located in Rio Grande do Sul at the Instituto de Pesquisas e Experimentação Agropecuárias do Sul. Four sources of phosphorus were applied to the soil at the rate of 90 kg/ha of P2O5. Periodically the various fractions of phosphorus were determined. From the data obtained in the laboratory and the production of rice the following suggested studies are made: 1. Transformations that occur in the soil with added phosphorus. 2. Comparison between the forms of phosphorus in the soil and their availability. 3. Relation between the availability of phosphorus and the production of rice.